Advancing banana and plantain R & D in Asia and the Pacific Vol. 10: Proceedings of the 10th INIBAP-ASPNET Regional Advisory Committee meeting Bangkok, Thailand, 10-11 November 2000 - Molina, A.B.; Roa, V.N.; Maghuyop, M.A.G. (2001)
On the occasion of the 10th congress, the INIBAP-ASPNET network and the national research centres review banana growing in the South-East Asian countries and the Pacific islands. Achievements and ongoing programmes are discussed for each country. The new prospects are then described, allowing for the results obtained, producers' requirements and the problems encountered in the field. The main limiting factors for banana growing are examined for each country: the main constraints are fungal diseases, nematodes and pests. The multiplication and distribution of healthy plant material and the introduction of resistant and/or tolerant hybrids is drawing keen interest from producers. Finally, prospection and the collection and conservation of banana germplasm form an important component of breeding and varietal creation. Seventeen communications.